Insulectomy for Refractory Epilepsy: Case Series and Literature Review - Rodrigues, Adriano de Medeiros Barbosa; Bernardo, Henrique Nicola Santo Antonio; Seba, Maria Clara Cardoso; Junior, Carlos Alberto de Almeida Castro; Franceschini, Paulo Roberto; Aguiar, Paulo Henrique Pires de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Surgical resection of the insula (insulectomy) is a procedure used for brain lesions and for refractory epilepsy. It has a difficult surgical access and the need of a wide anatomical knowledge and preoperative planning. There are two types of surgical approaches aiming the exposure of the insular cortex: transsylvian and transcortical. The importance of insulectomies is the efficacy in providing a remarkable decrease in seizures. The objective of the present article is to document the results of a series of 10 patients submitted to insulectomies for refractory epilepsies and compare them with the results of other studies reported in the literature, as well as to describe the main nuances of the surgical approaches and their associated risks. In the new case series, all patients corresponded to preoperative Engel classification IV for; after a mean 2-year follow-up period, they corresponded to Engel classification II. A subtotal resection was performed in six patients, and the remaining four underwent a partial resection, most of them leading to temporary complications. The literature review endorsed the good outcomes of the casuistry. A critical analysis of the presented data reiterates the opinion of several authors that insulectomies are beneficial and safe for the patients. A broad anatomical knowledge of the insular region, preoperative planning (limits of resections), and the use of modern microsurgical techniques must be considered as basic principles by neurosurgeons for the prevention of perioperative morbidities. Insulectomies are safe and effective, although they result in temporary postoperative complications, and provide highly satisfactory results in terms of seizure control.
Keywords: island of reil; insular cortex; refractory epilepsy; resective procedures